INTEGRATION OF “PLANETARY APPROACH” AND “PLANETARY JUSTICE” WITHIN THE ARCTIC OCEAN GOVERNANCE SYSTEM TO EMBRACE THE ROLE OF NON-HUMAN NATURE IN PROTECTING THE ARCTIC MARINE ENVIRONMENT - Sabrina Hasan (International Journal of Law in Changing World)
The Arctic region has drawn attention from around the world due to its distinct environment and susceptibility to climate change. The need for an effective system of governance that goes beyond anthropocentric viewpoints is more pressing than ever as human activities in the region increase, from resource exploitation and shipping to tourism. The incorporation of a “planetary approach” into the Arctic Ocean Governance System is examined in this paper, which represents a paradigm change that is crucial for safeguarding the Arctic marine environment. The paper further explores how the concepts of “planetary approach” and “planetary justice” can be integrated into the Arctic Ocean governance system to embrace the role of non-human nature in protecting the Arctic marine environment. In addition, the paper analyses how the “planetary approach” with a broader mandate can implement best practices in Arctic Ocean governance.